Evaluasi Penjadwalan Proyek Pengembangan Rumah Sakit Mitra Husada Pringsewu - Dharmawan, Weka Indra; Oktarina, Devi; Wibowo, Tito Catur (MEDIA KOMUNIKASI TEKNIK SIPIL, 2017)
Project is a unique sequence of interrelated activities to achieve particular result and done in particular time period. Due to time and budget limitation, management undertaking of a project needs to be evaluated by using a special method in order to avoid loss and retardation. CPM and S Curve are among evaluation methods. This study was to identify network, critical activities, critical event, critical line and to analyze optimum cost and duration of VVIP Building development project of Mitra Husada Hospital Pringsewu with time acceleration to avoid retardation. Result showed that after S Curve Evaluation done, implementation cost could be reduced 10% lower than realization cost from IDR 12,423,077,000.00 to be IDR 11,293,707,000.00. Mean while, after acceleration by using CPM method, the critical line decreased from three to one line and project duration shortened from 448 days to be 360 days. Evaluation of projects using the S Curve and with the CPM shows a simple way of evaluation and can be done by various actors of construction.